Strategy of the Dikdasmen Council of PDM Asahan to Improve the Professionalism of PAI Teachers at Muhammadiyah Schools in East Kisaran District - Ahmad Mustaqim; Asnil Aidah Ritonga; Sakti Ritonga (Didaktika: Jurnal Kependidikan, 2024)
This study discusses the strategies of the Dikdasmen Council of PDM Asahan to enhance the professionalism of Islamic Education teachers at Muhammadiyah schools in the East Kisaran District. The issue addressed in this study is the professionalism of PAI teachers in performing their duties, which does not meet the professional standards expected, particularly in pedagogical skills and teaching administration, as assessed by the Dikdasmen Council of PDM Asahan. This study employs a qualitative approach. Qualitative research is designed to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts, both individually and in groups. One type of descriptive qualitative research is case study research. the findings obtained in the field, both from interviews and library research, the root of the problem identified is that the pedagogical competence of teachers, including PAI teachers, is not entirely satisfactory, with a percentage of 70%. The common issues related to teacher professionalism include: Limited use of IT-based learning media among teachers, Understanding student characteristics during teaching, The delivery of learning materials that do not engage students, Teaching administration issues, such as teaching not aligning with their qualifications and insufficient mastery of the curriculum.